The adhesive system and root canal region do not influence the degree of conversion of dual resin cement - Pereira, Priscilla Cristoforides [UNESP]; de Melo, Renata Marques [UNESP]; Chaves, Carolina [UNESP]; Galhano, Graziela A. P. [UNESP]; Bottino, Marco Antonio [UNESP]; Balducci, Ivan [UNESP] (Universidade de São Paulo (USP), Faculdade de Odontologia de Bauru, 2010)
Objectives: The aim of this study was to evaluate the influence of two adhesive systems and the post space region on the degree of conversion of dual resin cement and its bond strength to root dentin. Material and Methods: One three-step etch-and-rinse (All-bond 2, Bisco) and another one-step self-etch (Xeno III, Dentsply) adhesive systems were applied on 20 (n=10) crownless bovine incisors, at 12-mm-deep post space preparation, and a fiber post (DT Light Post, Bisco) was cemented using a dual cure resin cement (Duo-Link, Bisco). Three transverse sections (3 mm) were obtained, being one from each study region (cervical, middle and apical). The degree of conversion of the dual cure resin cement was determined by a micro-Raman spectrometer. The data (%) were submitted to repeated-measures analysis of variance and Tukey's test (p<0.05). Results: For both groups, the degree of conversion means (%) (All bond 2(cervical) = 69.3; All bond 2(middle) = 55.1; All bond 2(apical) = 56; Xeno III(cervical) = 68.7; Xeno III(middle) = 68.8; Xeno III(apical) = 54.3) were not significantly different along the post space regions (p<0.05). Conclusions: Neither the adhesive nor the post space region influenced the degree of converstion of the cement layer.
Keywords: Root canal; Resin Cements; Raman spectroscopy; Adhesives